Social Capital, Public Spending and the Quality of Economic Development: The Case of Italy - Fabio Sabatini (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper carries out an empirical assessment of the relationship between social capital and the quality of economic development in Italy. The analysis draws on a dataset collected by the author including about two hundred variables representing different aspects of economic development and four structural dimensions of social capital. The quality of development is measured through human development and indicators of the state of health of urban ecosystems, public services, gender equality, and labour markets, while social capital is measured through synthetic indicators representing strong family ties, weak informal ties, voluntary organizations, and political participation. The quality of development exhibits a strong positive correlation with bridging weak ties and a negative correlation with strong family ties. Particularly, the analysis shows a strong correlation between informal ties and an indicator of social well-being (synthesizing gender equality, public services and labour markets) and between voluntary organizations and the state of health of urban ecosystems. Active political participation proves to be irrelevant in terms of development and well-being. Finally, the role of public spending for education, health care, welfare work, and the environment protection is analysed, revealing a scarce correlation both with social capital and development indicators.
Keywords: O15; O18; R11; Z13; 330; Social capital; Social networks; Public spending; Economic development; Human development; Principal component analysis